PENGARUH FRAUD TRIANGEL DALAM MENDETEKSI FINANCIAL STATEMENT FRAUD PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA SELAMA PERIODE 2013- 2015 - Suri Novira; Yesi Mutia Basri; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The aim of this research was to analyze the fraud risk factors of the fraud triangle (pressure, opportunity, and rationalization) in detecting the likelihood of financial statement fraud. The variables of the fraud triangle used is pressure consisting of negative cash flow from operation (NCFO), the factor opertunity is audit comittee size (ACSIZE) and rationalization are proxied by auditor change (AUDCHENGE). Indication financial statement fraud in this research uses a proxy Beneish M-Score as the dependent variable. The population of this research is the mining company listed in Indonesian Stock Exchange. Total sample was 27 companies the period of 2013 to 2015. Testing the hypothesis used the logistic regression method. The result of this study indicate that only a factor of pressure consisting of a negative cash flow (NCFO) effect the financial statements fraud. While other factors are opportunities proxied by the audit committee size (ACSIZE) and rationalization proxied by auditor change (AUDCHANGE) does not affect the financial statement fraudKeywords: financial statement fraud, fraud triangle, pressure, opportunity, rationalization.